An Engineered Synthetic Biologic Protects Against Clostridium difficile Infection - Vedantam, Gayatri; Kochanowsky, Joshua; Lindsey, Jason; Mallozzi, Michael; Roxas, Jennifer Lising; Adamson, Chelsea; Anwar, Farhan; Clark, Andrew; Claus-Walker, Rachel; Mansoor, Asad; McQuade, Rebecca; Monasky, Ross Calvin; et al. (Frontiers in Microbiology, 2018)
Morbidity and mortality attributed to Clostridium difficileinfection (CDI) have increased over the past 20 years. Currently, antibiotics are the only US FDA-approved treatment for primary C. difficile infection, and these are, ironically, associated with disease relapse and the threat of burgeoning drug resistance. We previously showed that non-toxin virulence factors play key roles in CDI, and that colonization factors are critical for disease. Specifically, a C. difficile adhesin, Surface Layer Protein A (SlpA) is a major contributor to host cell attachment. In this work, we engineered Syn-LAB 2.0 and Syn-LAB 2.1, two synthetic biologic agents derived from lactic acid bacteria, to stably and constitutively express a host-cell binding fragment of the C. difficile adhesin SlpA on their cell-surface. Both agents harbor conditional suicide plasmids expressing a codon-optimized chimera of the lactic acid bacterium’s cell-wall anchoring surface-protein domain, fused to the conserved, highly adherent, host-cell-binding domain of C. difficile SlpA. Both agents also incorporate engineered biocontrol, obviating the need for any antibiotic selection. Syn-LAB 2.0 and Syn-LAB 2.1 possess positive biophysical and in vivo properties compared with their parental antecedents in that they robustly and constitutively display the SlpA chimera on their cell surface, potentiate human intestinal epithelial barrier function in vitro, are safe, tolerable and palatable to Golden Syrian hamsters and neonatal piglets at high daily doses, and are detectable in animal feces within 24 h of dosing, confirming robust colonization. In combination, the engineered strains also delay (in fixed doses) or prevent (when continuously administered) death of infected hamsters upon challenge with high doses of virulent C. difficile. Finally, fixed-dose Syn-LAB ameliorates diarrhea in a non-lethal model of neonatal piglet enteritis. Taken together, our findings suggest that the two synthetic biologics may be effectively employed as non-antibiotic interventions for CDI.